Extended New Generalized Lindley Distribution - Shibu, D. S.; Irshad, M. R. (Statistica, 2016)
In this paper, we consider an extended version of new generalized Lindley distribution (NGLD). We refer to this new generalization as the extended new generalized Lindley distribution (ENGLD). A comprehensive account of the mathematical properties of the new distribution including estimation is presented. A real life data set is considered here to illustrate the relevance of the new model and compared it with other forms of Lindley models using method of moment estimation and method of maximum likelihood estimation.